Assessing the Effectiveness of Regional Policy Responses to Mass Redundancies: The Case of the Illawarra Region, Australia. Issue 2 (7th February 2019) - O'Brien, Martin; Burrows, Scott
Abstract : Regional economies historically reliant on large‐scale manufacturing are particularly susceptible to episodes of mass employee redundancies. This was evident in the case of the Illawarra region in 2011 following the announcement of BlueScope Steel to close one of its two remaining blast furnaces. In common with recent closures of large manufacturers in regional Australia, the Federal Government reacted with policies to help redundant workers obtain reemployment as well as investment attraction strategies to create employment in the region. The research presented here uses a longitudinal and mixed methods approach to analyse the effectiveness of these policies. We uncovered a number of deficiencies in the implementation and evaluation of these policies and offer a number of recommendations with respect to programme flexibility, stakeholder representation and government transparency.